2005
DOI: 10.1128/aem.71.10.5929-5934.2005
|View full text |Cite
|
Sign up to set email alerts
|

Concentrations of Pathogens and Indicators in Animal Feces in the Sydney Watershed

Abstract: A fecal analysis survey was undertaken to quantify animal inputs of pathogenic and indicator microorganisms in the temperate watersheds of Sydney, Australia. The feces from a range of domestic animals and wildlife were analyzed for the indicator bacteria fecal coliforms and Clostridium perfringens spores, the pathogenic protozoa Cryptosporidium and Giardia, and the enteric viruses adenovirus, enterovirus, and reovirus. Pathogen and fecal indicator concentrations were generally higher in domestic animal feces t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
102
3
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(109 citation statements)
references
References 29 publications
3
102
3
1
Order By: Relevance
“…There are only limited reports on the concentration and environmental loading of Giardia cysts as a result of faecal contamination by sheep. One study reported that the range of cyst shedding for adult sheep in Sydney catchments was 0 -504 cysts g -1 with a median of 26 cysts g -1 (Cox et al, 2005). However this was based on immunomagnetic separation (IMS) with recovery rates varying from 13-73%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are only limited reports on the concentration and environmental loading of Giardia cysts as a result of faecal contamination by sheep. One study reported that the range of cyst shedding for adult sheep in Sydney catchments was 0 -504 cysts g -1 with a median of 26 cysts g -1 (Cox et al, 2005). However this was based on immunomagnetic separation (IMS) with recovery rates varying from 13-73%.…”
Section: Discussionmentioning
confidence: 99%
“…Cyst transport to surface water can occur by deposition of manure directly in the water or by wash-off in surface runoff. Current risk management practices for minimizing pathogen health risks to water supplies require both prevalence and the concentration of pathogens in faeces to establish pathogen source loads in watersheds, enabling the assessment of risk from faecal contamination of source waters (Cox et al, 2005). Accurate quantification of Giardia cysts in animal faecal deposits on land is an essential starting point for estimating catchment Giardia loads.…”
Section: Introductionmentioning
confidence: 99%
“…A more recent survey of domestic animals and wildlife showed that the concentration of C. perfringens spores was 2.9 × 10 5 in pigs, 4.6 × 10 3 in poultry, and 3.6 × 10 5 and 3.3 × 10 6 per gram in dogs and cats. High concentrations were detected in domestic animals but rarely in wildlife [34].…”
Section: Discussionmentioning
confidence: 99%
“…Les résultats des tests d'hypothèse sont également confirmés par les analyses (GRAVES et al, 2007;MEALS, 1992;PAtNI et al, 1985). Les CF mesurés à ces stations peuvent provenir des déjections des animaux d'élevage, des humains et de la faune dont le contenu typique en CF varie de 10 6 à 10 10 uFC•100 mL -1 (ASAE, 1998;COx et al, 2005;MDDEP, 2009b). Des sources de CF d'origine non fécale existent également, comme Klebsiella dans les rejets de papetières, absents des sous-bassins versants de la présente étude, ainsi que Enterobacter et Citrobacter (SBSC, 1992) et des souches de E. coli adaptées à l'environnement (kON et al, 2009).…”
Section: Relations Incluant La Densité Humaineunclassified